Pengembangan Uji Tes dengan Menggunakan Quizizz pada Masa Covid-19 di MTs Nurul Huda Baros - Nina, Nina Nismatun Hasanah; Mu’izzuddin, Moch (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2022)
The background of the research is the factual circumstances at the Islamic Intermediate Madrasah Tsanawiyah Nurul Huda Baros in teaching vocabulary, using manual testing on papers without the Internet in the form of subjective testing and objective testing only. So it is not suitable under epidemiological conditions. The aims of this research are; 1) To get acquainted with the teaching of Arabic vocabulary for students at Madrasah Tsanawiyah Nurul Huda Baros. 2) To learn about the development of the Arabic language test using Quizizz during the Corona pandemic at Madrasah Tsanawiyah Nurul Huda Baros. 3) To determine the effectiveness of developing a vocabulary test in teaching Arabic using Quizizz during the pandemic at Madrasah Tsanawiyah Nurul Huda Baros. 4) To know the advantages and disadvantages of developing a vocabulary test using Quizizz in Madrasah Tsanawiyah Nurul Huda Baros. In the context of this research, the researcher developed an Arabic language assessment test with the type of research and development (Research & Development) Analyze model: ADDIE, Design, Development, Implementation, Evaluation steps (Evaluation). The researcher chose this step because it has straightforward procedural steps for developing educational methods, books, and strategies. Effectiveness using Quizizz shows that test results are in percentage values based on the mean value of the pre-and post-test. There are significant differences, the cardiac test score is 61.4%, and the test score is 82%. Based on the test account. Ttabel 1,68385 and Thitung 6,18778. So indicates that the vocabulary test has increased significantly after using Quizizz methods.